2017
DOI: 10.1017/age.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of Coastal Beach Safety Information-Seeking Behavior

Abstract: We estimate a bivariate probit model using data from a survey of Maine and New Hampshire beachgoers to (i) assess the impact of exposure to and contact with beach waters on safety information-seeking behaviors, and (ii) compare information-seeking behaviors for surf conditions and water quality information. We find that individuals who engage in certain high-contact recreation activities (i.e., swimming, fishing, surfing) are more likely to seek out safety information and that some potential drivers of this be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…Also, respondents visiting the beach for reasons not involving contact with the water and/or less-influenced by weather were less likely to give an affirmative WTP response. The effect of reason for visiting is consistent with the findings of Kaminski et al (2017), who found that beachgoers who engage in activities that do not involve contact with water tend not to seek out beach conditions information. The likelihood of an affirmative WTP response increases significantly with the number of information types of interest to respondents, the expected number of additional good beach days resulting from access to beach information, and the level of confidence that the survey will influence availability of the app.…”
Section: Econometric Modelsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, respondents visiting the beach for reasons not involving contact with the water and/or less-influenced by weather were less likely to give an affirmative WTP response. The effect of reason for visiting is consistent with the findings of Kaminski et al (2017), who found that beachgoers who engage in activities that do not involve contact with water tend not to seek out beach conditions information. The likelihood of an affirmative WTP response increases significantly with the number of information types of interest to respondents, the expected number of additional good beach days resulting from access to beach information, and the level of confidence that the survey will influence availability of the app.…”
Section: Econometric Modelsupporting
confidence: 86%
“…evidence that this may be the case for beach visits (Kaminski et al 2017;Murray, Sohngen, and Pendleton 2001;Pendleton, Martin, and Webster 2001;and Penn et al 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To prevent drowning accidents due to rip currents, previous studies have focused on placing warning signs, lifesaving surveillance, and beach ags, to indicate the safe swimming areas, or rip currents and other hazards (Ménard et al, 2018). However, studies that have evaluated the effectiveness of signs suggest that less than half of the beachgoers are not aware of signs posted on the beach (Matthews, Andronaco, & Adams, 2014;Brannstrom et al, 2015;Kaminski et al, 2017). It has also been suggested that many people did not prepare for or avoid rip currents, even if they were aware of the warning signs (Siegrist & Gutscher, 2006;Karanci, Aksit, and Dirik, 2005;Hall & Slothower, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Beaches are great attractions for people to visit in leisure activities, such as running, surfing and swimming, and directly influence the economy, mainly in countries with tropical climate (1) . However, activities at sea require attention, as they can be the scene of accidents and shark attacks, which more commonly occur in hot seasons, where the sea surface temperature favors the presence of animals, and because there is greater movement of people in aquatic recreation activities.…”
Section: Introductionmentioning
confidence: 99%